1987
DOI: 10.1243/pime_proc_1987_201_115_02
|View full text |Cite
|
Sign up to set email alerts
|

A Parameter Sensitivity Analysis for the Dynamic Model of a Variable Displacement Axial Piston Pump

Abstract: Sensitivity analysis is applied to an investigation of the influence of parameters on the dynamics of a variable displacement axial piston pump. Since an exact mathematical model of piston pump is complex and highly non-linear, the investigation of its dynamic characteristics for the variation of the system purameters by changing separate parameter values in sequence becomes very inefective. In this paper a parameter sensitivity analysis was employed to analyse the eflects of the system parameters systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…The angle of the swash plate, a, is controlled with a hydraulic servo-system that is attached to the swash plate by a mechanical arm of length L. The forces of the servo system are resisted by a naturallyinduced torque on the swash plate, T, that results from the pumping action of the pump itself. Since it has previously been shown that the inertia of the swash plate is negligible compared to the stiffness of the servo system (Kim et al, 1987;Zeiger and Akers, 1986), the moments on the swash plate can be …”
Section: (7)mentioning
confidence: 99%
See 1 more Smart Citation
“…The angle of the swash plate, a, is controlled with a hydraulic servo-system that is attached to the swash plate by a mechanical arm of length L. The forces of the servo system are resisted by a naturallyinduced torque on the swash plate, T, that results from the pumping action of the pump itself. Since it has previously been shown that the inertia of the swash plate is negligible compared to the stiffness of the servo system (Kim et al, 1987;Zeiger and Akers, 1986), the moments on the swash plate can be …”
Section: (7)mentioning
confidence: 99%
“…Until recently, little has been known about the driving forces of the swash plate itself in open literature and, perhaps, Zeiger and Akers (1985) are to be credited for the pioneering work in this area. Since the work of Zeiger and Akers, other research regarding the dynamics and control of the swash plate has appeared in the literature (Manring and Johnson, 1994;Schoenau et al, 1990;Kim et al, 1987;Zeiger and Akers, 1986). All of this work has contributed to a better understanding of the variable-displacement pump and to a better understanding of the hydrostatic transmission as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [10] conducted a study on the sensitivity of the outlet pressure control to certain parameters within the pump system, and the total torque on yoke due to the force of pumping pistons and bias pistons was given. However, the high-frequency swash plate oscillation was not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a Local Sensitivity Analysis (LSA) to a nonlinear variable displacement axial piston pump model was applied to study parameter sensitivities and to reduce model order (Kim et al, 1987), and to a linear water quality model (Pastres et al, 1997). In LSA, parameters …”
Section: Introductionmentioning
confidence: 99%